Suppurative Intracranial Complications of Pediatric Sinusitis: A Single-Center Experience. (21st September 2020) - Otto, William R; Paden, William Z; Connors, Meghan; Joerger, Torsten; Buzi, Adva; Rizzi, Mark; Huh, Jimmy; Storm, Phillip; Heuer, Gregory; Kennedy, Benjamin; McGuire, Jennifer; Swami, Sanjeev; et al.
Abstract: Background: Suppurative intracranial complications of sinusitis are rare events in children and can lead to harmful neurologic sequelae and significant morbidity. We sought to review the presentation and management of patients admitted at our hospital with these conditions. Methods: This was a retrospective study of pediatric patients admitted to a quaternary children's hospital from 2007 to 2019 for operative management of sinusitis with intracranial extension. Clinical characteristics, including surgical and microbiological data, were collected and analyzed. Results: Fifty-four patients were included; the median age was 11.0 years, and there was a male predominance. Eighty-nine percent of patients had prior healthcare visits for the current episode of sinusitis; 46% of patients had an abnormal neurologic exam on admission. Epidural abscess and subdural empyema were the most common complications, and subdural empyema was associated with repeat surgical intervention. The dominant pathogens were Streptococcus anginosus group organisms (74%). The majority of patients completed treatment parenterally, with a median duration of therapy of 35 days. Neurological sequelae, including epilepsy or ongoing focal deficits, occurred in 22% of patients. History of seizure or an abnormal neurological exam at admission were associated with neurological sequelae. Conclusions: Clinicians should consider intracranial complications of sinusitis in patients with symptoms of sinusitis for >1 week. Patients should undergo urgent neuroimaging, as neurosurgical intervention is essential for these patients. Subdural empyema was associated with repeat neurosurgical intervention. Neurological sequelae occurred in 22% of patients, and new onset seizure or an abnormal neurological exam at admission were associated with neurological sequelae. Abstract : We describe the presentation and management of a pediatric cohort treated for sinusitis with intracranial extension. Patients were treated with neurosurgical drainage and prolonged antibiotic therapy. Streptococcus anginosus spp. were common. Neurological sequelae occurred in one-fifth of children.